FORMULASI PROSES PEMBUATAN SOYGURT DENGAN PENAMBAHAN EKSTRAK BUAH NAGA MERAH (Hylocereus polyrhizus) - Carolyne Eka Meylani; Deny Utomo (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2025)
This study aimed to improve the soyghurt recipe by incorporating red dragon fruit extract (Hylocereus polyrhizus), which is rich in betacyanins, vitamin C, and fiber, to enhance color, aroma, and flavor. The research method used was a Completely Randomized Design (CRD), with varying concentrations of red dragon fruit extract: 10, 20, 30, and 40 parts, replicated three times. Parameters analyzed included ash content, pH, viscosity, total soluble solids, lactic acid bacteria count, and organoleptic assessment (color, aroma, texture, and taste). Data analysis was performed using ANOVA and Tukey's test, as well as the Friedman test for organoleptic data. The findings showed that the best treatment was recorded at a concentration of 10% (P1) with a pH of 4.41, a viscosity of 376 cP, an ash content of 1.04%, a total soluble solids of 4.0%, and a lactic acid bacteria count of 7.50 × 10⁸ CFU/mL, which meets the standard probiotic criteria (≥10⁷ CFU/mL). The organoleptic evaluation results showed that the addition of red dragon fruit extract significantly impacted color, aroma, texture, and taste. Treatment P4 (40%) received the highest scores for color (4.44), aroma (4.36), and taste (4.20), while the best texture was achieved by P1 (10%) with a score of 3.96, indicating that higher concentrations can improve color and taste but can decrease viscosity. These findings suggest that incorporating red dragon fruit extract into soyghurt formulation not only enhances its sensory qualities but also maintains its probiotic standards. The 10% concentration is recommended as the optimal formulation for balancing physicochemical stability and consumer preference.